2010
DOI: 10.1007/s11430-010-0043-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal evolution of Beijing 2003 SARS epidemic

Abstract: Studying spatio-temporal evolution of epidemics can uncover important aspects of interaction among people, infectious diseases, and the environment, providing useful insights and modeling support to facilitate public health response and possibly prevention measures. This paper presents an empirical spatio-temporal analysis of epidemiological data concerning 2321 SARS-infected patients in Beijing in 2003. We mapped the SARS morbidity data with the spatial data resolution at the level of street and township. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…(2) Mathematical statistical analysis of epidemiological data, such as quantitative analysis for temporal individual cases, close contacts and control measures using classical mathematical statistical methods [6,7]. (3) Spatial-temporal statistical analysis of SARS epidemic characteristics, including exploring the distribution patterns of SARS cases in spatial-temporal scales [8], analyzing the spatial autocorrelation and heterogeneity characteristics of SARS epidemic using spatial-temporal statistical methods [9][10][11], and exploring the spatial pattern, temporal process, and driving factors of SARS epidemic using meta models combining multiple spatial-temporal statistical methods [12]. (4) simulation and prediction of SARS epidemic process based on network dynamic models, such as simulating and analyzing the SARS epidemic process using system dynamics and multi-agent system [13,14], and simulating the spread mechanisms based on models of small-world network and scale-free network [15,16].…”
mentioning
confidence: 99%
“…(2) Mathematical statistical analysis of epidemiological data, such as quantitative analysis for temporal individual cases, close contacts and control measures using classical mathematical statistical methods [6,7]. (3) Spatial-temporal statistical analysis of SARS epidemic characteristics, including exploring the distribution patterns of SARS cases in spatial-temporal scales [8], analyzing the spatial autocorrelation and heterogeneity characteristics of SARS epidemic using spatial-temporal statistical methods [9][10][11], and exploring the spatial pattern, temporal process, and driving factors of SARS epidemic using meta models combining multiple spatial-temporal statistical methods [12]. (4) simulation and prediction of SARS epidemic process based on network dynamic models, such as simulating and analyzing the SARS epidemic process using system dynamics and multi-agent system [13,14], and simulating the spread mechanisms based on models of small-world network and scale-free network [15,16].…”
mentioning
confidence: 99%
“…Spatial interaction exists in the spatio-temporal transmission of an infectious disease [16]. The epidemiological mechanism interacting with socioeconomic factors at different spatial locations determines the variability of the geographical distribution of a disease [17]. The disparities of TB incidence were in uenced by geospatial factors, population and socioeconomic heterogeneity, which will further affect the migrant population [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that public health interventions such as early recognition, prompt isolation, and appropriate precautionary measures, could effectively limit spread of the virus. (2) Use of spatial statistics to explore the spatial clustering characteristics of SARS [12][13][14]. For example, some researchers used geostatistic, such as semivariogram, Moran's I and LISA statistics to study the risks of SARS transmission and spatiotemporal evolution in Beijing or Guangzhou.…”
Section: Introductionmentioning
confidence: 99%